IMPROVING MATHEMATICS LEARNING COMPLIANCE USING THE DISCOVERY METHOD IN CLASS II STUDENTS OF SD NEGERI 023 RAMBAH - Seri Harnani (STKIP Rokania Pasir Pangaraian, 2021)
This classroom action research was conducted at SD Negeri 023 Rambah, Rokan Hulu Regency in class II for the 2019/2020 school year. Actions are taken by applying the discovery method to improve students' mathematics learning mastery. Discovery learning method is a learning method that can improve students' thinking skills to solve the problems they face. By using the discovery method, student learning completeness in each cycle experiences changes and increases. This is proven by the achievement of pre-cycle test results, the average percentage is only 29.03% and at the end of the second cycle it reaches 87.10%. The application of the demonstration method can improve the competence of grade II students at SD Negeri 023 Rambah, Rokan Hulu Regency